Socioeconomic and Demographic Factors Associated With Mortality Before and During the COVID-19 Pandemic: An Analysis of 28 European Countries - Paola Sillitti; Paola Sillitti; Paola Sillitti; Paola Sillitti; Clément Meier; Clément Meier; Clément Meier; Olivier Mucchiut; Olivier Mucchiut; Olivier Mucchiut; Jürgen Maurer; Jürgen Maurer; et al. (International Journal of Public Health, 2025)
ObjectivesThe pandemic was the most significant event affecting health systems in the last 100 years. Research shows that gender, age and socioeconomic status were associated with higher mortality during the pandemic. However, most studies are cross-sectional and country specific. This paper assesses sociodemographic characteristics associated with time and cause of death in Europe between 2018 and 2022.MethodsThe analysis includes 7,137 decedents aged over 50, using post-death interviews with proxy respondents, from the Survey on Health, Ageing, and Retirement in Europe (SHARE). Data from 28 countries, from SHARE waves 7 to 9, are examined using t-tests, chisquaretests and multivariate logit regression models, controlling for sociodemographic characteristics. The three binary outcome variable sindicate the time and cause of death.ResultsBeing male, older, without a partner, self-reporting financial difficulties, and living in Eastern Europe were associated with an increased likelihood of dying during the pandemic. The association was stronger for deaths due to COVID-19, respiratory and infectious diseases.ConclusionThe pandemic highlighted socioeconomic gradients in mortality. These results call for policymakers to prepare for future shocks, ensuring equal access to adequate care.